Bilateral congenital triangular alopecia associated with alopecia areata: report of two cases. - Purva, Lakhotiya; Het, Modi; Meghana, Phiske; Shylaja, Someshwar (European Journal of Pediatric Dermatology, 2026)
Congenital triangular alopecia (CTA), also known as temporal triangular alopecia or Brauer nevus may be present at birth or acquired during first decade of life with incidence of 0.1% . Presentation at birth and at age of 2-9 years, is seen in 36.5% and 55.8% respectively. There is no gender predilection and it affects mainly white patients. It is usually unilateral in 80%, more commonly described on the left side and rarely described bilaterally. It can present as triangular, oval, or lancet-shaped patch of alopecia. It may be misdiagnosed as traction alopecia, trichotillomania or tinea capitis. Histopathological and dermoscopic features help in its diagnosis. There is no effective treatment and, in most cases, there is no need for therapeutic intervention. Treatment modalities include topical Minoxidil, surgical excision, and hair transplantation. Eyebrow and eyelash alopecia is characterized by either complete or partial loss of eyebrow or eyelash hair. Prevalence of eyebrow and eyelash involvement is not precisely known. Etiologies are varied, and diagnosis is confirmed by dermoscopy and histopathology. Treatment modalities include topical and intralesional steroids, JAK inhibitors, and prostaglandin analogues. A 8 year old girl presented with well-demarcated, 13 × 12 × 10 cm, triangular patch of alopecia occupying bilaterally temporo-parieto-vertex region of scalp since birth, with patchy loss of hair in mid portion of both eyebrows and complete loss of eyelashes in both lower eyelid since 2 years. There was alopecia areata (AA) over scalp in mother. Dermoscopy confirmed the diagnosis of CTA and AA. A 9-year-old girl presented with well demarcated, oval, 5x5 cm patch of hair loss on occipital scalp since 1 month, triangular patch of hair loss bilaterally on temporo-parietal scalp since birth with scanty eyebrows and eyelashes. No similar family history. Dermoscopy confirmed CTA with AA. Both cases were given Minoxidil for CTA and topical corticosteroids for all AA lesions. Both CTA and eyebrow, eyelash alopecia are rare condition, with bilateral presentation of CTA being rarer. Co-existence of both these is hitherto unreported. Trichoscopy aids in diagnosis of both. Prompt treatment helps prevent/reverse progression of hair loss in both.